KESEDIAAN MEMBAYAR (WILLINGNESS TO PAY) TERHADAP PRODUK COFFEE LATTE DI KOTA SEMARANG - Sutan Mhd Amin Jamal; Edy Prasetyo; Kustopo Budiharjo (University of Jember, 2020)
The development of the coffeeshop grew rapidly in the last 10 years, with the change of adolescent lifestyle patterns in consuming coffee in the coffeeshop. Coffee Latte is one of the usual menu served by the coffeeshop at varying prices. This research aims to analyze the characteristics of consumers, analyzing the value of Willingness to Pay and analyzing the influence of consumer characteristics against the value of consumer Willingness to Pay on coffee latte products. The study was conducted on 15 January to 15 February 2020 located in the coffeeshop around the campus Undip Tembalang with the determination of the location purposive. The research method used is the survey method. Respondents were taken as much as 99 people using accidental sampling. Data collection using primary and secondary data. Analysis of the data used are descriptive analysis, quantitative analysis and the analysis of logistic regression. The results of the study gained that most consumers of coffee latte were men with a percentage of 58.6% and women with a percentage of 41.4%. Consumers who are willing to pay more than the current price are 94.9% of respondents and amounting to 5.05% of the respondents are not willing to increase by 5% to 25%. A significant factor affecting the willingness of pay is quality. Keywords: Coffee Latte, Willingness to Pay, Consumers